TEMPO-functionalized zinc phthalocyanine: synthesis, magnetic properties, and its utility for electrochemical sensing of ascorbic acid. Issue 7 (14th January 2016) - Eken Korkut, Sibel; Akyüz, Duygu; Özdoğan, Kemal; Yerli, Yusuf; Koca, Atıf; Şener, M. Kasım
Abstract : Zinc(ii ) phthalocyanine (TEMPO-ZnPc ), peripherally functionalized with 2, 2, 6, 6-tetramethyl-1-piperidinyloxy (TEMPO) radicals is synthesized and its magneto structural and electrochemical sensing properties are investigated. Abstract : Zinc(ii ) phthalocyanine (TEMPO-ZnPc ), peripherally functionalized with 2, 2, 6, 6-tetramethyl-1-piperidinyloxy (TEMPO) radicals is synthesized and its magneto structural and electrochemical behaviors are investigated.TEMPO-ZnPc shows multi-electron ring based reduction reactions and a TEMPO based oxidation reaction. Spectroelectrochemical measurements support these peak assignments.TEMPO-ZnPc is tested as a homogeneous and heterogeneous ascorbic acid (AA) sensor. Disappearance ofTEMPO-ZnPc based reduction processes and the observation of new waves at around 0 and 1.20 V with respect to increasing AA concentration indicate the interaction ofTEMPO-ZnPc with AA and usability of the complex as an electrochemical AA sensor. For practical usage as heterogeneous electrocatalysts for AA sensing, a glassy carbon electrode (GCE) is coated withTEMPO-ZnPc (GCE/TEMPO-ZnPc ) and this modified electrode is tested as a heterogeneous AA sensor. The redox peak of GCE/TEMPO-ZnPc at 0.81 V decreases the peak current while a new wave is observed at 0.65 V during the titration of the electrolyte with AA. GCE/TEMPO-ZnPc sense AA with 1.75 × 10 −6 mol dm −3 LOD with a sensitivity of 1.89 × 10 3 A cm mol −1 .